Answer:
The answer to your question is:
22.- P1 ( -4, -7) P2 (0, 3)
23.- P1 ( 4, 9) P2 (-4, -7)
Explanation:
22.-
y = x - 3
y = -x² + 9
Solve it by substitution
x - 3 = -x² + 9
x² + x - 3 - 9 = 0
x² + x - 12 = 0
( x + 4)(x - 3) = 0
x1 = - 4 x2 = 3
Finally
y1 = -4 - 3 x2 = 3 - 3
y 1 = -7 x2 = 0
P1 ( -4, -7) P2 (0, 3)
23.- y = 2x + 1
y = x² + 2x - 15
Substitution
2x + 1 = x² + 2x - 15
x² + 2x - 2x - 15 - 1 = 0
x² = 16
x = ± 4
x1 = 4 x2 = -4
y1 = 2(4) + 1 y2 = 2(-4) + 1
y1 = 9 y2 = -7
P1 ( 4, 9) P2 (-4, -7)